Effect of acidic environment on the response of endothelial cells to irradiation: Implications for microbeam radiation therapy. (April 2014) - Kim, So-Ra; Kim, Eun-Hee
Abstract Purpose: Microbeam radiation therapy (MRT) is a novel experimental radiotherapy regimen, which delivers high doses of synchrotron-generated X-rays in the form of quasi-parallel arrays of microbeam separated by microplanar spaces. The repair or healing of irradiated regions (Peak) via migration of endothelial cells (EC) from unirradiated regions (Valley) plays an important role in the response of tumors and normal tissues to MRT. It is known that intratumor microenvironment is acidic. We investigated the influence of environmental acidity on the response of EC to ionizing radiation. Materials and methods: Effects of irradiation on the viability, clonogenicity and migration rate of endothelial cells were studied using human umbilical vascular endothelial cells and mouse endothelial cells in pH 7.3 and 6.4 environments. Results: An exposure to acidic environment (pH 6.4) for 2–4 days exerted little effect on the viability of EC. On the other hand, acidic environment significantly retarded the migration of control and irradiated EC. The migration of EC into 2000 μm-wide wound was slower than that into 1000 μm-side wounds. Conclusion: The microenvironmental acidity and the size of beam opening in MRT may greatly affect the repair of irradiated peak regions via migration of EC from unirradiated valley regions.